The structural, electronic, elastic, phonon, and thermodynamical properties of the SmX (X = P, Sb, Bi) compounds - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
A detailed theoretical study of structural, electronic, elastic, phonon, and thermodynamical properties of SmX (X = P, Sb, Bi) compounds is presented by performing ab-initio calculations based on density-functional theory using the Vienna ab-initio simulation package (VASP). For describing the interaction between electrons and ions, the projector-augmented wave (PAW) method is used. The generalized-gradient approximation (GGA) is chosen for the exchange-correlation functional. The calculated structural parameters, such as the lattice constant with and without spin-polarization (SP), bulk modulus, cohesive energy, second-order elastic constants, the electronic band structures and the related total density of states with and without SP and spin-orbit coupling (SOC) are presented. The high-pressure phase of all compounds is investigated and phase transition pressure from NaCl (B1) to high-pressure phase is determined. For B1 structure, the calculated values of lattice constants are compared with the available experimental and other theoretical data and bulk modulus values are compared with available other theoretical results. In order to gain further information, we have calculated Zener anisotropy factor (A), Poisson's ratio (nu), Young's modulus (E), shear modulus (C), elastic wave velocities, Debye temperature, phonon frequencies and one-phonon density of states for B1 structure of these three compounds. The temperature dependent behavior of heat capacity and entropy for these compounds in B1 phase is also presented. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Elastic properties; Lattice dynamics; Thermodynamical properties; Electronic band structure; Ab-initio calculation; NACL-TYPE STRUCTURE; INITIO MOLECULAR-DYNAMICS; TOTAL-ENERGY CALCULATIONS; WAVE BASIS-SET; HIGH-PRESSURES; PHASE-TRANSITIONS; AB; CONSTANTS; PSEUDOPOTENTIALS; PHOTOEMISSION